FTIR Transmission Spectra of Crude Oil of Some Absheron Peninsula Enterprises - Pashayev, A.M.; Valiyev, N.A.; Asgarov, K.A.; Musayev, A.A.; Mammadov, I.Kh.; Allahverdiyev, K.R. (Herald of Azerbaijan Engineering Academy, 2024)
Fourier Transform Infrared (FTIR) spectroscopy provides useful information about different chemical inclusions in crude oils. In particular, the presence or absence of hydrocarbon functional groups may be qualitatively determined. It is known that in the Republic of Azerbaijan there are 12 oil-gas production companies, including 8 owned by Azerbaijan and 4 owned by Joint Stock Companies. In most cases of oil spillage, it is desirable to have more than one analytical technique for detecting source of suspected spilled crude oil and its properties. In our previous publications, we reported results of the laser induced fluorescence and the Raman spectra analyses of crude oil samples taken from the 12 oil-gas production companies in Azerbaijan and discussed their distinctive features across observed spectra. In the present paper, we give results of the FTIR transmission spectra of crude oil samples taken from the 6 oilgas production companies in the Republic of Azerbaijan.